Patterns and Determinants of Youth Health-Seeking Behavior - Clarinda L. Berja, Grace T. Cruz and (Philippine Social Sciences Review; Social Sciences and Health Issue, Ed. Carmen C. Jimenez, 2010)
The 1994 Young Adult Feltility Survey (YAFS) has shown that many Filipino Adolescents have Reproductive Health Problems (RHPs) but do not seek medical care when they experience serious problems. Moreover, the study shows a relatively low but significant level of premarital sexual activity particularly among male adolescents. Yet contraceptive practise remains low with condoms mostly commonly sourced from drugstores and withdrawal as their preferred FP methods. The findings tend to suggest that the adolescents are unaware of the dangers posed by their sexual exposure and their RHPs, thus their reluctance to seek medical assistance. These have clear implications for policies and programs designed to improve the well-being of adolescents.